Polinizadores da aceroleira (Malpighia emarginata DC., Malpighiaceae) em área do Triângulo Mineiro : riqueza de espécies, nicho trófico, conservação e manejo - Vilhena, Alice Maria Guimarães Fernandes (2009)
Bees are considered the most important pollinators of native plants and crops. In some cultures, they can increase the production and the fruit quality. Thus, studies that address issues of pollinators conservation and management like populations monitoring and knowledge about trophic resources are crucial. In this work, we present parameters that can support the conservation and management of the West Indian Cherry s pollinators, the Centridini bees. The data were collected in a cultivation of this plant, in Água Limpa Experimental Station, Uberlândia, MG, during October-November (P1) and January-February (P2) of the years 2006/2007 (A1) and 2007/2008 (A2 ), totaling 54 hours per year of observation. Moreover, the rate of natural pollination was accompanied. It was verified a richness of 23 species. Centris (Centris) varia and Centris (Centris) aenea were the most frequent species in the A1 and A2 respectively. We recorded 20 species in the A1 and 18 species in the A2, which showed temporal variation during the flowering. However, the number of visits did not differ significantly between the two periods in both years. The data show a replacement of species that pollinate effectively the West Indian Cherry, which presents a compensatory effect in which one species reduces the impact of the lack of another for the plant. There was no correlation of the number of fruits with the number of visits, the number of species and the number of visits per hour. This is believed to have been a richness and a frequency of pollinators equivalent to the threshold needed to keep a low variation in the fruit production. This is mainly due to the presence of preserved areas of Cerrado in the neighborhood of that culture, which provides sites for nesting and food resources for these species. In the pollinic loads analysis of seven Centridini bees collected from 2004 to 2008 in the same culture, we found grains of 41 plant species and five pollinic types belonging to 18 families. Malpighiaceae was the most representative family and with Solanum lycocarpum, the most important resource source. Among the main nectar sources, Distictella elongata and Caesalpinia peltophoroides stood out. The latter plus S. lycocarpum, Type Heteropteris 3, Type Byrsonima and M. emarginata, were used by all bee species, although they have been found in different abundances. It was verified the participation of 29 species that are presented as isolated pollen. Centris (Centris) flavifrons showed the largest trophic niche width and the most uniformity in the use of resources. The species with smallest width and with less uniformity was C. (C.) varia, whose pollinic load showed 72,04% of M. emarginata grains. The maximum similarity in the use of plant sources was 88% between C. (C.) aenea and C. (C.) spilopoda. Probably, the Malpighiaceae species in the area of cultivation are helping in the fruit set, ensuring large populations of pollinating species. The maintenance of plant species found in this study is essential to the West Indian Cherry s pollinators conservation and management in Cerrado areas. This interaction network based on pollination services helps not only the crop production, but also the reproduction of plants that co-occur in the same site, are dependents of pollinators and are sources for such Centridini.